Direct hydrogenation of amides to alcohols and amines under mild conditions - Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Shimon, Linda J. W.; Milstein, David (Journal of the American Chemical Society, 2010)
The selective, direct hydrogenation of amides to the corresponding alcohols and amines with cleavage of the C−N bond was discovered. The expected products of C−O cleavage are not formed (except as traces in the case of anilides). The reaction proceeds under mild pressure and neutral, homogeneous conditions using a dearomatized, bipyridyl-based PNN Ru(II) pincer complex as a catalyst. The postulated mechanism involves metal−ligand cooperation by aromatization−dearomatization of the heteroaromatic pincer core and does not involve hydrolytic cleavage of the amide. The simplicity, generality, and efficiency of this environmentally benign process make it attractive for the direct transformations of amides to alcohols and amines in good to excellent yields.